Harmonical oscillator and electro-mechanical analogy: an interdiscinary experiment to high precision mass variation measurements - Watanabe, Ailton M. [UNESP]; Santos, Adriano dos [UNESP]; Bueno, Paulo Roberto [UNESP] (Editora Unesp, 2009)
De forma geral, os cursos de física clássica oferecidos nas universidades carecem de exemplos de aplicações nas áreas de química e biologia, o que por vezes desmotivam os alunos de graduação destas áreas a estudarem os conceitos físicos desenvolvidos em sala de aula. Neste texto, a analogia entre os osciladores elétrico e mecânico é explorada visando possívies aplicações em química e biologia, mostrando-se de grande valia devido ao seu uso em técnicas de medição de variação de massa com alta precisão, tanto de forma direta como indireta. Estas técnicas são conhecidas como técnicas eletrogravimétricas e são de especial importância em aplicações que envolvem biossensores. Desta forma, o texto explora o estudo da analogia eletromecânica de forma interdisciplinar envolvendo as áreas de física, química e biologia. Baseado nessa analogia é proposto um experimento que permite a sua aplicação em diferentes níveis conceituais dessas disciplinas, tanto em abordagem básica como mais profunda.

In general, the traditional Physics courses needs examples of the aplications of the Physics concepts in other areas such as Chemistry and Biology. This lacks tend to demotivate Chemistry and Biology students regarding to deal with Physical concepts developed in classroom. In this work, the analogy among mechanic and electric oscillators is investigated to be applied in Chemistry and Biology areas, showing to be valuable due to its aplication in techniques that aims to measure mass variation with high precision. This measure could be made in a direct or indirect way. These techniques are known as electrogravimetric techniques and they are important in biosensor aplications. Thus, this paper explores the electromechanic analogy in an interdisciplinary way involving areas like Physics, Chemistry and Biology. Based on this analogy, it is proposed an experiment that can be applied in different ways, i.e. by an basic approach or more deeper, depending on the students specific formation, in other words, Physics, Chemistry or Biology.
Keywords: Oscilador massa-mola; oscilador RLC; equivalência eletromecânica; oscilador piezoelétrico; eletrogravimetria; Block-spring oscillator; RLC oscillator; eletromechanical analogy; piezoelectric oscillator; electrogravimetry